"An analysis of the principle: "changing of rulings should not be denied by the change of times - Al- Ramahi, Ahmed Saeed Salem (Journal of Islamic Sciences, 2019)
The aim of this study is to properly investigate some of what is distinguished about the Islamic Sharia comparing to the earthly rules in terms of the reliability of its rules as well as the flexibility and accessibility to any time or place. The study also highlights a very important aspect of foundation science which is applying the Sharia rules on the issues that encounter people. This is because Allah issues rules and obligations to be applied on humans as a real and not make it an extreme image in the minds. The researcher studied the principle " changing of rulings should not be denied by the change of times"” a applicable and fundamental study. Although this principle is well- known with later Fiqh scholars, it has opened up fundamental and Fiqh dimensions that need to be examined staring from the statement of the principle and the consequences following that. Thus, this study comes to answer the following questions:To what extent we have to take this principle into guarantee based on the changing of the rules, and due to the change of times and traditions? What is the sharafundamental by which this principle is built? what is the clue behind applying these rules, and the nature of these rules that are changeable and the nature of this change?The most prominent results of this study are list below:1- The researcher believes that the statement of this principle should be changed as “The change of effort rulings do not mistaken by the sources” this is to avoid any problematic or ambiguity on this principle.2- The area of applying this principle is in the changing parts and not on the certainties.
Keywords: disallow; time; customs; adequate; hard; variable; reality